Diversity of Mycotoxins in Stored Paddy Rice: Contamination Patterns in the Mekong Delta, Vietnam - Lien Thi Kim Phan; Thuy Thi Ngoc Nguyen; Thien Thi Thanh Tran; Sarah De Saeger (Toxins)
Rice (Oryza sativa L.) is the most important food in Vietnam. However, rice is often lost in post-harvest due to fungal growth and mycotoxins contamination. This study aimed to evaluate mycotoxin contamination in stored paddy rice collected in 2018, 2019, and 2022 in six provinces in Mekong Delta, Vietnam, using LC-MS/MS. The results revealed that 47% of the samples were contaminated with 12 types of mycotoxins. The prevalence of these mycotoxins was 30% (ZEN), 10% (FUS/MON), 6% (BEA/AFB2), 2–4% (AFG1, AFB1, AFG2), 2% (FB1), and 1% (OTA/AME/ENB). Among the provinces, stored paddy rice from Kien Giang had the highest contamination, followed by Ben Tre, Long An, An Giang, Dong Thap, and Can Tho. Remarkably, paddy rice collected in 2022 was usually contaminated with emerging mycotoxins with a higher incidence of co-occurrence ranging from 2–6% of the samples. Additionally, five stored paddy rice samples were contaminated with levels of AFB1, OTA, and ZEN exceeding Vietnamese regulatory limits for unprocessed rice. Our findings provide valuable insights into mycotoxin contamination across different years and growing regions in the Mekong Delta, Vietnam. This study could give essential information to stakeholders, including policy-makers or food safety authorities, etc., to inform strategies to mitigate these toxins in the near future and underscores the importance of monitoring rice production.